ANALISIS ANTROPHOMETRI DESAIN MEUBEL RUANG BELAJAR PAUD (STUDI KASUS PADA TK AL KHOIR SURAKARTA) - Hapsari, Putri Sekar; Purnomo, Agung (Institut Seni Indoensia Surakarta, 2015)
The good education tools and infrastructure becomes one of the important components in supporting the improvement of national education system. Furniture is one of the supporting tools. Furniture is designed to support the user’s activities in this case, they are children. It means that if their physicsgrow in accordance to their ages, consequently, the table and the chair must be suitable to their size. When it is ignored, it will influence their physical growing and decreases relieve their concentration in the learning process because of the uncomfortablefurniture and it even can influence their health. This research aims to get a description of furniture design in the early children’s study room in PAUD/ TK AL KHOIR Surakarta based on the erghonomy and anthropometry. The children table, chair, and shelf become the research focus because the furniture directly in touch with the children when they have learning process in class.The research uses the method of descriptive with qualitative and quantitative approach or namely the multiple strategy of research. It means that it uses various methods in solving the research problems.Quantitative approach is meant to use numeric data resulted from the field measurement observation, then it is compared with the referred reference and analyzed based onresearcher’s interpretation sourced from field analysis. The result of this research shows that during this time, anthropometry size used in furniture making has commonly been suitable with the children size of 6 to 7 years. Otherwise, there is still a note that is the table width needs to be increased, the hip seat and the backrest need to be adapted to the form of children hip bone and backbone or it can be given foam in order to make comfortable when the children sit for a long time. The shelf size has been suitable with the children’s reach.Keywords: Anthropometry, furniture, PAUD (pre elementary school)